Pemidanaan Anak Sebagai Pelaku Tindak Pidana Pembunuhan - Dwi Putri Melati (Universitas Bandar Lampung (UBL), 2015)
Child who committed the crime of murder as provided by Article 339 Penal Code in conjunction with Article 26 Paragraph (1) and (2) of Law No. 3 of 1997 on Juvenile Justice, problems concerning; Criminalization criminal murder committed by a child in the case of Register No. 791 / pid.a / 2012 / pn.tk andthe consideration of judges of criminal case of murder committed by a child in the case of Register No. 791 / pid.a / 2012 / pn Tk. The perpetrator is a child, then Article 339 Penal Code in conjunction with Article 26 paragraph(1) and (2) of Law No. 3 of 1997 on Juvenile Court sentenced imprisonment of 10 tahun.Pertimbangan judges based on: Facts law, psychology of law for the offender of child, Restorative justice. BAPAS their accompanying defendant and opinions regarding the case. The perpetrator was a child, Fulfillment of criminal elements. It burdensome, and relieve, not found a justification nor forgiving. resulting in death. Need to increase the professionalism of law enforcement officers, particularly Judges, prosecutors and police in the case of children. Granting sanction to pay attention to the child's physical, psychological and sociological child sanctions against Children do as a last effort.